2003
DOI: 10.1002/dc.10260
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology and immunocytochemistry in the diagnosis of 24 gastrointestinal stromal tumors: A quick, reliable diagnostic method

Abstract: The diagnosis of gastrointestinal stromal tumors (GISTs) is generally established on histopathologic examination of surgical specimens. Fine-needle aspiration (FNA), performed under the guidance of ultrasound or computed tomography, is being used with increasing frequency in an attempt to diagnose primary and/or metastatic GISTs before surgery. The present study was undertaken to characterize the cytological appearance of these tumors and to assess the role of cytology, together with immunocytochemistry (ICC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
1
26
2
Order By: Relevance
“…Other authors also have showed that, by combining smears and cell blocks with immunocytochemical studies, the samples obtained from EUS-FNA are highly accurate and efficient for a conclusive diagnosis of GIST. [19][20][21] Gastrointestinal stromal tumors strongly express positivity for ckit, and this reaction is necessary to name a tumor a GIST. Up to 70% of GIST lesions can also express positivity to CD34, and between 20% and 30% react with smooth muscle actin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors also have showed that, by combining smears and cell blocks with immunocytochemical studies, the samples obtained from EUS-FNA are highly accurate and efficient for a conclusive diagnosis of GIST. [19][20][21] Gastrointestinal stromal tumors strongly express positivity for ckit, and this reaction is necessary to name a tumor a GIST. Up to 70% of GIST lesions can also express positivity to CD34, and between 20% and 30% react with smooth muscle actin.…”
mentioning
confidence: 99%
“…Up to 70% of GIST lesions can also express positivity to CD34, and between 20% and 30% react with smooth muscle actin. 20 Despite those characteristics, it remains difficult to differentiate a benign from a malignant GIST solely on the basis of FNA samples because some features of malignant GIST such as mitotic index (>5/50 high-power fields), tumor necrosis, and nuclear pleomorphism may not be fully and accurately assessed in cytologic materials. 19 The presence of kit mutations in GISTs is a predictive factor of malignant behavior, but its absence does not completely rule out malignancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Seidal and Edvardsson [22] showed strong positivity for CD117 and CD34 on cytospin preparations of material aspirated from six GISTs. Lozano et al [9] performed ICC on PAP-stained smears from 24 GISTs with results comparable to those on cell blocks and surgical specimens. We have previously described good ICC results from our cytopathology laboratory in other tumors [23].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for CD117 is a sensitive marker for confirmation of the diagnosis of GIST, and its utility has been demonstrated on cytological specimens, including cell blocks and FNA smears [6,7,8,9,10,11,12,13]. However, approximately 5-15% of GISTs are immunonegative for CD117, leading to false-negative results [1,3,5,14].…”
Section: Discussionmentioning
confidence: 99%